The Restrictions of Human Rights During COVID-19 Pandemic. / Restricciones a los derechos humanos durante la pandemia COVID-19. - HARISOVICH MINGAZOV, LENARIS; ALEXEYEVICH SINYAVSKIY, ALEXEY (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In 2020, the world is faced with COVID-19 pandemic as one of the worst global catastrophes of the 21st century. The governments of countries around the world have introduced various emergency rules on the territory of their states as a measure to contain the pandemic. Are such restrictions permissible and how justified were they? Did the restrictions imposed comply with the norms enshrined in international human rights standards? Have states managed to strike a balance between “legality” and “necessity”? We will try to answer all these questions in this paper.RESUMEN En 2020, el mundo se enfrenta a la pandemia COVID-19 como una de las peores catástrofes mundiales del siglo XXI. Los gobiernos de países de todo el mundo han introducido varias reglas de emergencia en el territorio de sus estados como medida para contener la pandemia. ¿Son permisibles tales restricciones y cuán justificadas están? ¿Las restricciones impuestas cumplieron con las normas consagradas en los estándares internacionales de derechos humanos? ¿Han sido exitosos los estados en lograr un equilibrio entre "legalidad" y "necesidad"? Intentaremos responder a todas estas preguntas en este documento.